(untitled) (Leviathan (São Paulo), 2014)
This article analyzes some paradigmatic cases of tension between conflict and cooperation, limited cooperation and difficulties in initiating processes of cooperation in Central Asia, particularly in terms of water and electricity, often generating rivalries that prevent significant advances in regional integration